PHYSIOLOGICAL AND ANATOMICAL CHANGES OF PREGNANCY IMPLICATIONS FOR ANAESTHESIA – A RANDOMIZED CONTROLLED TRIAL - PANIGRAHI, SARMISTHA; PEETHANI, SANDHYA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The article aims at gaining in-depth knowledge of physiological and anatomical changes in pregnancy. Methods: A randomized controlled trial was done among 200 pregnant woman in Department of Obstetrics and Gynecology at Tertiary care institute and hospital for the period of 6 months (November 2021 to April 2022). Random Number table was used for selection of patients who were followed for pregnancy in the department. All demographic details and Pre-Anesthetic checkups were done. Statistical analysis was done using the software Statistical Package for the Social Sciences (SPSS) 22.0 version. This consecutive series of original research papers were reviewed for the reporting of ethics committee approval and patient consent. Results: Respiratory physiology continues to change throughout pregnancy. Airway resistance decreases 50% due to the effects of progesterone on bronchial smooth muscle. With Minute ventilation, RR, Tidal volume, and Alveolar ventilation are increased. Anatomically, diaphragm elevates with cephalad pressure of the growing gravid uterus, and the chest wall diameter increases in the anteroposterior and transverse diameters. This leads to unchanged Total Lung Capacity, Vital Capacity, and CC, while Expiratory Reserve Volume, Residual volume, and Functional residual capacity seen a decreased in 20% in all patients. Blood volume increases early in gestation (at approximately 12 weeks), continues to increase rapidly during the second trimester and more slowly during the remainder of pregnancy. Cardiac output increases in early pregnancy with changes measurable by 8 weeks gestation. Conclusion: Minute ventilation, RR, Tidal volume, and Alveolar ventilation are increased. Cardiac output increases in the early pregnancy with changes measurable by 8 weeks gestation. Cardiac output increases most rapidly (to approximately 35% above baseline) during the second trimester, then remains about the same until term. Output increases substantially with labor contractions; each contraction increases cardiac output an additional 10–25%.